Changes in Income Distributions and the Role of Tax‐Benefit Policy During the Great Recession: An International Perspective1. (29th June 2017) - Bargain, Olivier; Callan, Tim; Doorley, Karina; Keane, Claire
Abstract: In this paper, we examine the impact of the economic crisis and the policy reaction on inequality and relative poverty in four European countries: France, Germany, Ireland and the UK. The period examined, 2008–13, was one of great economic turmoil, yet it is unclear whether changes in inequality and poverty rates over this time period were mainly driven by changes in market income distributions or by tax‐benefit policy reforms. We disentangle these effects by producing counterfactual ('no reform') scenarios using tax‐benefit microsimulation and representative household surveys for each country. For the first stage of the Great Recession, we find that the policy reaction contributed to stabilising or even decreasing inequality and relative poverty in the UK, France and, especially, Ireland. Market income changes nonetheless pushed up inequality and relative poverty in France. Relative poverty increased in Germany as a result of policy responses combined with market income changes. Subsequent policy reforms, in the later stage of the crisis, had markedly different cross‐country effects, decreasing overall poverty in France, increasing it in Ireland, and giving mixed effects for different subgroups in Germany and the UK.